Diagnosis of the conflict over the use and occupation of land and areas protected by law in rural properties in the Municipality of Monte Carmelo-MG (Revista Espinhaço, 2024)
This research aims to carry out an exploratory analysis of geospatial data to evaluate the state of justice of rural properties declared in the CAR (Rural Environmental Registry) of the municipality of Monte Carmelo (MG) in compliance with the guidelines of the Forest Code (Law 12,651/2012). This analysis helps rural producers understand the need to recover areas and support forest restoration strategies in the municipality. SiCAR and MapBiomas databases were used. Analyze the overlap between rural properties, conflicts of land use and coverage within the protected areas in properties - Permanent Preservation Areas (APP) and Legal Reserves (RL), the size of these properties in order to verify the profile of rural properties and its forest conservation status. The design of area overlap statistics was carried out using QGIS® software. The analyzes revealed that 10.76% of the property polygons have overlapping areas in SiCAR. The area in non-compliance with the Legislation was 63.83% (APPs) and 68.56% (RLs). Forest restoration actions must prioritize areas in conflict with Forestry Legislation. The information found in this study is technical support for prioritizing forest restoration according to Law 12,651/2012 in the municipality.
Keywords: Forest Code; Nature Conservation; Environmental Regularization